Conexão digital e desconexão social : impactos do uso constante de telas nas interações sociais e no desenvolvimento infantil - Lubian, Bianca Costa (2025)
This article analyzes the impacts of the constant use of screens on overall child development and on children’s social interactions. The study aims to understand how this exposure occurs, when it becomes excessive, and how digital devices can have positive or negative effects. To this end, a bibliographic study was conducted based on recent research. The results indicate that prolonged screen use may reduce opportunities for social interaction and, consequently, negatively affect child development. It is concluded that the mediating role of caregivers is necessary to ensure a balanced use of technology by children, promoting healthy practices in order to minimize potential harm to child development.